An Analysis of Feminism Issues in Veronica Roth's Divergent: A Reader Response Study - Andi Darmawanto; Masulah -; Ari Setyorini (Tell : Teaching of English Language and Literature Journal, 2018)
Since this research mainly uses a reader response approach in which the response from the readers becomes the main data to analyze, two College students with different background and gender become the subject of the research to contribute their interpretation. Moreover, they are engaged in WhatApp group as a mean to discusse about the issues which become the guide of the research. Futhermore, this research has its focus to scrutinize the response of the readers toward feminism issues in Veronica Roths Divergent. Beside that, reader-response theory authored by Wolfgang Iser to be the main theory which guides to determine the type of the readers. Their responses transcribed by the researcher are the main data to complete the aim of the research. By utilizing descriptive qualitative method to describe the interpretation, the yield of this research is that the readers interpret the issues of womens leadership, gender discrimination, and independent female in the novel of Divergent by collaborating their background; experiences, gender and prior knowledge as prime-effect on how they interpret.Â